2020
DOI: 10.1093/toxsci/kfaa074
|View full text |Cite
|
Sign up to set email alerts
|

Lead Impairs the Development of Innate Lymphoid Cells by Impeding the Differentiation of Their Progenitors

Abstract: Lead (Pb) is a heavy metal toxic to the immune system, yet the influence of Pb on innate lymphoid cells (ILC) remains to be defined. In this study, we found that occupationally relevant level of Pb exposure impaired ILC development at the progenitor level by activating Janus Kinase1. C57BL/6 mice treated with 1250 ppm, but not 125 ppm Pb acetic via drinking water for 8 weeks had reduced number of mature ILC, which was not caused by increased apoptosis or suppressed proliferation. Conversely, Pb increased the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“… 158 Furthermore, long-term low-dose lead exposure in mice results in reduced bone density and trabecular bone. 158 Lead suppresses proliferation of HSCs 159 and myeloid and lymphoid differentiation 160 , 161 in mice. In contrast, human smokers have increased numbers of monocytes and granulocytes and comparable levels of lymphocytes to nonsmokers.…”
Section: Lifestyle Factors and Their Influence On Hsc Nichesmentioning
confidence: 99%
“… 158 Furthermore, long-term low-dose lead exposure in mice results in reduced bone density and trabecular bone. 158 Lead suppresses proliferation of HSCs 159 and myeloid and lymphoid differentiation 160 , 161 in mice. In contrast, human smokers have increased numbers of monocytes and granulocytes and comparable levels of lymphocytes to nonsmokers.…”
Section: Lifestyle Factors and Their Influence On Hsc Nichesmentioning
confidence: 99%
“…Mechanisms associated with these effects involve higher expressions of interferon regulatory factor-8 (IRF8), which blocks C/EBPα and modulates neutrophil differentiation [ 230 ]. Recent evidence shows that exposure to Pb at occupational levels can result in lower numbers of innate lymphoid cells (ILCs) in the blood of mice, with this effect being dependent on activation of Janus Kinase-1 leading to an inability of BM CLP progenitors to become mature and be delivered into the bloodstream [ 231 ]. CLPs differentiate into innate lymphoid cell-restricted progenitors via transcription factor ID2, which further differentiate into mature ILC 1, 2, and 3 [ 232 ].…”
Section: Cellular and Molecular Mechanisms Of Toxicity On Hematopomentioning
confidence: 99%
“…Environmental pollutants can significantly impact hematopoiesis [ 17 , 18 ]. We previously reported that heavy metals in the living environment such as cadmium, lead, and Hg significantly influenced the function of HSCs and the committed progenitors, leading to aberrant myelopoiesis and/or lymphopoiesis [ 19 , 20 , 21 , 22 , 23 ]. In terms of Hg, we found that Hg 2+ impacted the proliferation of HSCs and critically relied on IFNγ-dependent on BM-resident macrophages (MΦ); Hg 2+ increased the number of progenitors for granulocytes and MΦ in the BM of B10.S mice [ 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%